Aplicação do "Software" PFA (Patients Flow Analysis) no Setor de Doenças Sexualmente Transmissíveis e Assistência ao Adolescente - Goulart Filho, Rubem de Avelar; Gouvêa, Tegnus Vinicius Depes de (Brazilian Journal of Sexually Transmitted Diseases, 1995)
The utilization of PFA (Patient Flow Analysis - a computer software) by STD branch enabled the authors to analyze as quality the worth of patients’ assistance. Also the unit cost of patient and professionals could be evaluated.